Histologis Perkembangan Embrio Ayam pada Masa Inkubasi Satu sampai Tujuh Hari - Fitriani Fitriani; Husmimi Husmimi; Dian Masyitha; Muslim Akmal (Agricultural Faculty, 2021)
ABSTRAK. Penelitian ini bertujuan melihat perkembangan embrio ayam secara histologi pada waktu 1, 2, 3, 4, 5, dan 7 hari inkubasi. Sampel yang digunakan adalah telur fertil yang didapat dari teaching farm Fakultas Pertanian Jurusan Peternakan Universitas Syiah Kuala. Pengamatan secara makroskopis dilakukan pada setiap sampel embrio ayam, sementara pengamatan mikroskopis struktur embrio ayam dilakukan dengan pembuatan preparat histologi. Hasil penelitian ini menampilkan data perkembangan embrio ayam secara spesifik dari umur inkubasi hari ke-1 sampai hari ke-7. Secara makroskopik dan mikroskopis, gambaran umum perkembangan embrio ayam selaras dengan informasi tabel pertumbuhan embrio ayam. Secara histologis, gambaran perkembangan struktur embrio ayam baru dapat diamati dengan baik yaitu pada umur inkubasi hari ke-3 sampai hari ke-7. Dapat disimpulkan bahwa secara histologi perkembangan embrio ayam baru dapat diamati pada masa inkubasi hari ke-3. Penelitian ini juga dapat dijadikan sebagai bahan acuan dasar untuk penelitian lanjutan terutama terhadap organogenesis pada embrio ayam. (Histological evaluation on the development of chicken embryo during the incubation periodfrom 1st to 7th days) ABSTRACT. The aim of this study was to find out the development of chicken embryos at day 1st, 2nd, 3rd, 4th, 5th, and 7th of incubation by histological method. The samples used were the fertile eggs obtained from the teaching farm of the Faculty of Agriculture, Department of Animal Husbandry, Syiah Kuala University. Macroscopic observations were made on each embryos sample, while microscopic observations of the embryos structure were carried out by histological preparations procedure. The results of this study presented the specific data of chicken embryos development from day 1st to day 7th of incubation. The macroscopic and microscopic data showed the general description of chicken embryos development similar to the information on the chicken embryo growth table. The microscopic results showed the structure description of the chicken embryos can be well observed at day 3rd to the day 7th of incubation. It can be seen the development of chicken embryos can be observed by histology method on day 3rd of incubation. This research can also be used as a basic reference for further research, especially on organogenesis of chicken embryos.